Neill’s mapping function simplification for dry component using regression methods - Hamzah, Sakidin; Siti Rahimah , Batcha; Asmala, A. (UTP PRESS, 2015)
The modeling of the GPS tropospheric delay mapping function should be revised by simplifying its mathematical model. The current tropospheric delay models use mapping functions in the form of continued fractions. This model is quite complex and need to be simplified. By using regression method, the dry (hydrostatics) mapping function models has been selected to be simplified. There are twenty six operations for dry mapping function component of Neill Mapping Function (NMF), to be carried out before getting the mapping function scale factor. So, there is a need to simplify the mapping function models to allow faster calculation and also better understanding of the models.